Research and application of forward and backward reasoning based on binary taxonomic key - SHEN Ai-hua; TANG Qi-yi; CHENG Jia-an (浙江大学学报. 农业与生命科学版, 2006)
The binary classification key, a kind of basic data structure is widely applied in the taxonomic identification of diseases and pests. For the sake of using the binary classification key more flexiblly to classify and identify the diseases and pests as knowledge reasoning, the integration of the principles of backward reasoning and two-way reasoning was put forward, which charges the binary key into the knowledge database of expert system, and computers can make use of the structure to search the branch node and realize the assistant identification of diseases and pests. The assistant expert system developed for diseases and pests identification and taxonomic study can carry out the diversified functions of the system, and meet various requests of users.